GNSS Practice in Survey Department - Timilisina, Sushmita; Nepal, Bibek (Journal on Geoinformatics, Nepal, 2019)
Control Networks for Nepal was originally defined through the use of conventional measurements. Conventional mapping methods have led to a static and inactive networks of control point. This network of control served us very well until the devastating earthquake hit Nepal and disturbed it. Determination of precise ground locations is essential for various tasks such as engineering works, earth observation, location-based technologies, emergency service providers, etc. Global Navigation Satellite System plays a very important role in providing quick and reliable positioning/navigation data. The term ‘global navigation satellite system’ (GNSS) refers to a constellation of satellites providing signals from space transmitting positioning and timing data. These systems use the principle of trilateration to calculate the location of a user, through the information obtained from a number of satellites. Each satellite transmits coded signals at precise intervals. In principle, three satellites must be available to determine a three-dimensional (x,y,z) position , additional fourth signal is necessary for precise location of a single point. This helps in eliminating the time differences between satellite’s atomic clocks and the receiver's clocks. USA in around 1970’s started the use of Global Positioning System(GPS). Geodetic Survey Division under Survey Department commenced the use of GPS technology in 1991 A.D as a method for survey technology. Survey Department initiated the use of GPS for carrying out survey of the previously established high order control points. Transformation Parameters (TP) between the National Co-ordinate System and WGS-84 System was derived using the initial Control points co-ordinate and co-ordinate of the same Control points obtained from GNSS survey. GNSS has been used for establishing, updating and rehabilitation of Control Network, measure shift in location produced by earthquake and for various survey task carried out by Survey Department.